In Vitro Evaluation of Occlusal Thickness On the Fracture Resistance of CAD-CAM Monolithic Zirconia Molar Crowns - Enas Khamakhim; Saleha Al Alwani (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives. Many dental practitioners have always struggled with obtaining aesthetic restorations while preserving the remaining dental structure. The purpose of this study is to investigate the relationship between the occlusal thickness and fracture resistance of CAD/CAM monolithic zirconia restorations to determine the feasibility of reducing the occlusal thickness, particularly in the posterior area, where inter-occlusal space is typically limited and high biting forces are applied. Methods. Four experimental groups were created using thirty-two CAD-CAM monolithic zirconia crowns with different occlusal thicknesses: 2.0 mm (group 1), 1.5 mm (group 2), 1.0 mm (group 3), and 0.5 mm (group 4). Self-adhesive resin cement was used to cement the restorations to human molars. Loading the specimens until fracture occurred, and the fracture resistance and mode of failure were recorded. The data were statistically analyzed using a one-way ANOVA followed by Fisher’s exact test. Results. All specimens’ fracture resistance values exceeded the maximum physiological occlusal loads in molar areas, and all of the crowns had consistent microcracks. A complete fracture was only interested in one crown with a thickness of 0.5 mm. Conclusion. The occlusal thickness of CAD-CAM monolithic zirconia crowns can be decreased to 0.5 mm while still being strong enough to sustain occlusal loads.